Calcitonin Gene-Related Peptide Downregulates Expression of Inducible Nitride Oxide Synthase and Caspase-3 after Intestinal Ischemia-Reperfusion Injury in Rats - Chih-Cheng Luo; Chen-Sheng Huang; Yung-Ching Ming; Shih-Ming Chu; Hsun-Chin Chao (Pediatrics and Neonatology)
Various investigations have demonstrated that calcitonin gene-related peptide (CGRP) plays an important role in mediating ischemic preconditioning. CGRP has been shown to mimic the protective effects of ischemic preconditioning and mitigate ischemia-reperfusion (I/R) injury in the heart, brain, gastrointestinal system, and other tissues. This study aimed to examine whether CGRP, a proven intestinal cytoprotective molecule, exerted its protective effects through modulation of inducible nitride oxide synthase (iNOS) and apoptosis after intestinal I/R injury. Methods: This animal study randomly divided 30 rats into the following five groups: (1) the normal control group, (2) the ischemia group with normal saline, (3) the I/R group with normal saline, (4) the ischemia group with CGRP (300 μg/kg), and (5) the I/R group with CGRP (300 μg/kg). Levels of iNOS messenger RNA (mRNA) and protein, and caspase-3 protein were determined by real-time quantitative polymerase chain reaction and Western blotting analyses, respectively. Statistical analysis was performed using analysis of variance with Dunn test. Results: The mRNA levels of iNOS increased after the intestinal ischemia or intestinal reperfusion phase (p < 0.01), and CGRP pretreatment significantly decreased iNOS mRNAs and protein levels (p < 0.01). The expression protein levels of caspase-3 increased after the intestinal ischemia or intestinal reperfusion phase. CGRP pretreatment significantly decreased the levels of caspase-3 proteins. CGRP intestinal cytoprotection is mediated, in part, by downregulation of expression of iNOS and caspase-3 after intestinal I/R injury. Conclusion: The study indicates that the cytoprotective role of CGRP (i.e., antiapoptotic effect) after I/R injury could be via downregulation of iNOS, which may relieve I/R tissue damage by blocking iNOS activity.